The Use of Peer Feedback toward EFL Students’ Writing Skill - Made Kencanadevi Nicahati (Universitas Majalengka, 2021)
This paper aimed to describe the implementation of peer feedback and how it can increase the writing skill of English as Foreign Language students. This paper is a library research. The method of this paper is descriptive qualitative method. The data were collected through analyzing papers, articles, and journals. The findings of this paper showed the reasons why peer feedback is useful toward writing skill of English as foreign language students. The students work collaboratively, minimizes errors, and saving time. The procedure of the strategy enables the students to work cooperatively in a group/peer. Peer feedback can be one solution to minimize the errors the students usually make in their writing before submit their writing draft to the teacher. The teacher can save much time in assessing the students’ work by conducting peer feedback in writing learning because the students’ work already corrected by their peer so it may have a little mistake left.